(3JcedI eKdKGJ bWQHs - (3GHf MHjHs; (3CHj Ydj Hf CMeO Hf GdeSJfjQ, bWQH,J (B206 (3g` s
(3ChdgG (B:s
(3GdCd hGdEd hGdCd s
(3BNQgG (B:s
(3hCeG GdbHGdI aGdMPGA MPGA hLgc Ci bHGdI hLgc s
(3cJHJ GdfSNI Hdhfjf ef GdeOGO CMOgeG XGgQ hGdCNQ ZjQ XGgQ HTcd hGVMs
(3hQO GdYfhGf GdCUdi ai c X (B2 / 1586s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(8844) s
Keywords: (3GddZIs